2020
DOI: 10.1002/erv.2765
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of brief and enhanced cognitive‐behavioural therapy for adults with non‐underweight eating disorders: A non‐randomized comparison

Abstract: Objective: Cognitive-behavioural therapy (CBT) is an efficacious and effective treatment for eating disorders, and is particularly valuable in the treatment of non-underweight cases (e.g., bulimia nervosa; binge eating-disorders). However, its recommended length for such cases (up to 20 sessions) makes it a relatively costly therapy. It has been suggested that a 10-session version (CBT-T) can also be effective, but there has been no direct comparison between the two forms (10 vs. 20 sessions). Method: This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 18 publications
(28 reference statements)
1
36
0
Order By: Relevance
“…This study found evidence supporting CBT-T effectiveness, while no interaction with eating disorder duration was found. Treatment effect appears similar to that reported by the protocol development team (Pellizzer et al, 2019a(Pellizzer et al, , 2019bTatham et al, 2020;Waller et al, 2018). The completion rate (65%) was also within the range (c. 50-69%) previously reported.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study found evidence supporting CBT-T effectiveness, while no interaction with eating disorder duration was found. Treatment effect appears similar to that reported by the protocol development team (Pellizzer et al, 2019a(Pellizzer et al, , 2019bTatham et al, 2020;Waller et al, 2018). The completion rate (65%) was also within the range (c. 50-69%) previously reported.…”
Section: Discussionsupporting
confidence: 87%
“…Three case series (Pellizzer, Waller, & Wade, 2019a, 2019b; Waller et al, 2018), and one non‐randomized comparison study (Tatham, Hewitt, & Waller, 2020) have found evidence of eating disorder psychopathology (Eating Disorder Examination Questionnaire: Fairburn & Beglin, 1994), and secondary impairment (Clinical Impairment Assessment: Bohn & Fairburn, 2008) reducing post CBT‐T, with medium‐large effect. While lack of randomized trial prevents direct comparison with other treatments, these results appear comparable to Fairburn's (2008) well‐established 20‐session CBT‐ED.…”
Section: Introductionmentioning
confidence: 99%
“…A sample of 40 will be sought, to allow for attrition at 47%, as found by Tatham et al (2020). Feasibility and attrition will be benchmarked around those figures.…”
Section: Participantsmentioning
confidence: 99%
“…CBT-T, a shorter 10-week version of CBT-E, was introduced for nonunderweight patients aiming to overcome the issues of costs, clinician time commitments, and waiting lists (Waller, Turner, Tatham, Mountford, & Wade, 2019). CBT-T's effectiveness and remission rates are comparable with longer versions of CBT-ED within health clinic settings (e.g., Fairburn, 2008), as shown by cohort studies and nonrandomized comparison studies (e.g., Pellizzer, Waller, & Wade, 2019;Tatham, Hewitt, & Waller, 2020;Waller et al, 2019), meaning that it has the potential to address the capacity issues that many services experience in managing caseloads.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, there has been considerable evidence for the benefits of brief forms of CBT-ED for nonunderweight patients, along with evidence that a brief form of group dialectical behaviour therapy (DBT) can be as effective as longer versions [ 67 ]. The development of a 10-session version of CBT-ED (CBT-T) [ 68 ] has been supported by case series and cohort comparison studies showing that this approach is as effective as 20-session therapy (e.g., CBT-E), with comparable outcomes at the end of treatment and at follow-up [ 30 , 69 , 70 , 71 ▪ ]. However, while these brief therapies offer rapid access to effective treatment for the majority of patients with eating disorders, there remains a very pressing need for further research into effective brief therapies for anorexia nervosa, speeding access and implementing effective treatments that take less than the current recommendation of up to 40 sessions of CBT-ED.…”
Section: Brief Cognitive-behavioural Therapies For Eating Disordersmentioning
confidence: 99%